Analisis Penerapan Stock Opname Terhadap Pengendalian Internal Persediaan: Pt Bub - Shakira, Naila; Widajantie, Tituk Diah (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Effective internal inventory control is essential for companies to ensure accurate and efficient inventory management. Stock taking is an important method of internal inventory control that aims to physically verify the quantity and value of inventory. This study aims to conduct an in-depth analysis of how the implementation of periodic stock opname contributes to the effectiveness of internal control and the accuracy of inventory data at PT BUB, a medium-sized retail company specializing in Hajj and Umrah souvenirs. The research employed a descriptive qualitative approach, using data collection techniques in the form of semi-structured interviews with key informants, as well as direct observations of the stock opname process in the warehouse and outlets. The data obtained were analyzed thematically and deductively through reduction, categorization, and interpretation processes, referring to the five components of the COSO Internal Control – Integrated Framework and the perspective of Agency Theory. The findings indicate that the implementation of periodic stock opname has proven to be an essential instrument in control and monitoring activities, enabling the detection of data discrepancies and minimizing the potential for fraud. Nevertheless, its effectiveness is still hampered by delays in transaction input, weak interdepartmental coordination, and limited adaptation to the new information system (SHAPE). These results reinforce empirical evidence that the integration of manual and digital controls, supported by a culture of discipline and effective communication, is the key to effective inventory control.